THE DOUBLE UNNOTIFICATION OF THE VULNERABLE RAPE CRIME DURING THE COVID-19 PANDEMIC IN BRAZIL - Caetano Albuquerque, Cinthya Maria (Revista Gênero e Interdisciplinaridade, 2021)
The crime of rape of the vulnerable occurs when the victim is unable to consent to sexual intercourse, since he is unable to offer resistance. To make rape effective, it is not necessary for the carnal conjunction to occur, since libidinous acts, such as touching genitals, are also considered for the configuration of the crime. The research is justified by analyzing the influence that social isolation has caused for the underreporting of cases of rape of the vulnerable.Thus, the article has as main objective to understand the social and legal aspects of the phenomenon of underreporting of rape of the vulnerable during the COVID-19 pandemic in Brazil. It is a research of a basic nature, whose method of approach used was inductive, with qualitative and quantitative analysis, developed through the technical procedures of documentation specific to bibliographic and documentary research. Among the results obtained, it was considered, finally, that the COVID-19 pandemic made victims of rape, especially vulnerable ones, even more susceptible to the practice of crime, while the underreporting of these cases grew, as the crime occurs in majority in the intrafamily supper, in a context of social isolation. It is necessary, then, to denaturalize the culture of rape and child sexualization, as well as to create effective public policies for the protection of infants, in order to encourage and enable access to justice, in addition to disseminating broad knowledge about the rights of children. children and adolescents.